2019
DOI: 10.1002/anie.201901318
|View full text |Cite|
|
Sign up to set email alerts
|

Illuminating the Function of the Hydroxyl Radical in the Brains of Mice with Depression Phenotypes by Two‐Photon Fluorescence Imaging

Abstract: Depression is intimately linked with oxidative stress. As one of the most reactive and oxidative reactive oxygen species that is overproduced during oxidative stress,t he hydroxyl radical (COH) can cause macromolecular damage and subsequent neurological diseases.However,due to the high reactivity and lowconcentration of COH, precise exploration of COH in brains remains ac hallenge.T he two-photon fluorescence probe MD-B was developed for in situ COH imaging in living systems.T his probe achieves exceptional se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 40 publications
0
41
0
Order By: Relevance
“…One such class of analytes are reactive oxygen species (ROS), which are associated with oxidative stress and as a result received much attention in the world of fluorescent probes for biological applications. 58,59 In 2019, a TP fluorescent probe for the detection of the ROS hydroxyl radical ( • OH) was developed by Tang et al 60 It is known that • OH can cause oxidative damage, which has been suggested to contribute to the pathogenesis of depression. The authors proposed that live monitoring of • OH in the brain is key to understanding this relationship, and of all the bioimaging tools two photon microscopy (TPM) would be the most advantageous.…”
Section: Methodsmentioning
confidence: 99%
“…One such class of analytes are reactive oxygen species (ROS), which are associated with oxidative stress and as a result received much attention in the world of fluorescent probes for biological applications. 58,59 In 2019, a TP fluorescent probe for the detection of the ROS hydroxyl radical ( • OH) was developed by Tang et al 60 It is known that • OH can cause oxidative damage, which has been suggested to contribute to the pathogenesis of depression. The authors proposed that live monitoring of • OH in the brain is key to understanding this relationship, and of all the bioimaging tools two photon microscopy (TPM) would be the most advantageous.…”
Section: Methodsmentioning
confidence: 99%
“…The TP turn-on probe 61 based on coumarin (Cou151) bearing a trifluoromethyl group as the TP reporter was developed to image in situ brain OH (Scheme 25). 34 With probe 61, 3-methyl-pyrazolone was chosen as the specific reaction site for OH. The one-electron oxidation reaction between OH and 3-methyl-pyrazolone, cleaved the electronwithdrawing ring and restored the push-pull electron effect of the coumarin ring.…”
Section: Two-photon (Tp) Excitation-based Fluorescent Sensors For Small Neutral Moleculesmentioning
confidence: 99%
“…In the past few decades, several analytical methods, including electron spin resonance (ESR) spectroscopy 22 , 23 , ultraviolet–visible (UV–vis) chromatography 24 , and fluorescence (FL) imaging 25 29 , have been devoted for the detection of •OH. Among them, FL imaging of •OH has attracted tremendous attention due to the advantage of high sensitivity, easy operation, rapid acquirement, and minimum invasiveness 30 32 .…”
Section: Introductionmentioning
confidence: 99%